Knowledge and perceptions of palliative care among cancer patients in a tertiary hospital - Mohd Arif Atarhim; NurulAsyiqin Ibrahim; Chong Zhi Yin; Santhna Letchmi Panduragan; Hamidah Hassan (Malaysian Journal of Medicine and Health Sciences, 2020)
Introduction: Early integration in palliative care for patients with advanced cancer has been correlated with an improvement quality of life, relieved depression while having survival benefits. Negative perceptions towards pal¬liative care or misconception about the idea of palliative care were reported as one of the causes for late referral by physicians. The aim of this study was to determine the knowledge and perception of palliative care among can¬cer patients in a tertiary hospital. Methods: A cross-sectional survey with populations of 139 cancer patients was conducted using convenience sampling. Quantitative data were collected by a structured questionnaire. A total of 92 responses were obtained. Results: Most of the participants were female (66.3%), Malay (71.7%) and attended secondary school (56.5%). The mean age of participants was 56.13 (±12.61) years while the mean income was RM 1944.20 (±2472.70). Majority of the participants had breast cancer (37.0%), followed by colorectal cancer (32.6%). Many of them were in stage IV (42.4%), followed by stage III (25.0%).Most of the cancer patients had a high level of knowledge and positive perception towards palliative care. They agreed that psychological, social and spiritual issues are a part of palliative care which helped to manage pain and other symptoms. Besides, responses portrayed positive perceptions of palliative care through the aspect of emotional reactions, cognitive reactions and palliative care needs. Conclusions: The current study has demonstrated that cancer patients in the tertiary hospital had better knowledge and perceptions in palliative care. High knowledge level and positive perception towards palliative care might increase the acceptance and palliative care practiced.